2010
DOI: 10.1051/0004-6361/200913509
|View full text |Cite
|
Sign up to set email alerts
|

Galactic winds and the symmetry properties of galactic magnetic fields

Abstract: Context. Contemporary studies of the symmetry properties of galactic magnetic fields contain two contradictory ideas. There are observational and theoretical hints that large-scale magnetic fields are symmetric with respect to the galactic plane in the disc, and antisymmetric in the halo. On the other hand, standard galactic dynamo models without a galactic wind give symmetric or antisymmetric configurations in both disc and halo regions simultaneously. Aims. Here we explore the role of a galactic wind in reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 13 publications
4
72
0
Order By: Relevance
“…This mean value agrees with theoretical predictions (e.g., Wielebinski & Krause 1993;Ferrière & Schmitt 2000;Moss et al 2010) and previous observations (e.g., Mathewson & Ford 1970;Heiles 2000;Men et al 2008). Analysis of NIR starlight polarimetry in the outer (Pavel et al 2012) and inner (Clemens et al 2012a) Galaxy also supports the conclusion that a single mean orientation is a reasonable characterization of the Galactic magnetic field in the disk.…”
Section: Starlight Polarimetry Toward Galactic Bubblessupporting
confidence: 92%
“…This mean value agrees with theoretical predictions (e.g., Wielebinski & Krause 1993;Ferrière & Schmitt 2000;Moss et al 2010) and previous observations (e.g., Mathewson & Ford 1970;Heiles 2000;Men et al 2008). Analysis of NIR starlight polarimetry in the outer (Pavel et al 2012) and inner (Clemens et al 2012a) Galaxy also supports the conclusion that a single mean orientation is a reasonable characterization of the Galactic magnetic field in the disk.…”
Section: Starlight Polarimetry Toward Galactic Bubblessupporting
confidence: 92%
“…However, model calculations of the mean-field αΩ-dynamo for a disk surrounded by a spherical halo including a galactic wind (Brandenburg et al 1993;and Moss et al 2010) simulated similar field configurations as the observed ones. Meanwhile, new MHD simulations of disk galaxies including a galactic wind are in progress and may explain the X-shaped field (Gressel et al 2008;Hanasz et al 2009a,b).…”
Section: Dynamo Action and Galactic Windmentioning
confidence: 57%
“…In the case of S100 model, the toroidal magnetic field component has a different direction above and below the disk plane, which indicates an odd (dipole-type) configuration of magnetic field with respect to the galactic plane. The odd symmetry of the magnetic field is not the preferred configuration in the disk geometry (Moss et al 2010), while it has been found in some galaxies (e.g., in NGC 4631, Krause 2003).…”
Section: Discussionmentioning
confidence: 88%